O'nyong-nyong Virus, Chad - Maël Bessaud; Christophe N. Peyrefitte; Boris A.M. Pastorino; Patrick Gravier; Fabienne Tock; Fabrice Boete; Hugues J. Tolou; Marc Grandadam (Emerging Infectious Diseases, 2006)
We report the first laboratory-confirmed human infection with O'nyong-nyong virus in Chad. This virus was isolated from peripheral blood mononuclear cells of a patient with evidence of a seroconversion to a virus related to Chikungunya virus. Genome sequence was partly determined, and phylogenetic studies were conducted.